VD_FINDINFO HC / 2016 / 644 vom 30. Mai 2016 - VD Tribunal cantonal (2016)
MAXIME OFFICIELLE, MAXIME INQUISITOIRE, PROTECTION DE L'ENFANT, PROTECTION DE L'UNION CONJUGALE | 176 al. 3 CC, 176 CC, 307 CC, 315a al. 1 CC, 315a CC